Identification of Tacca Chantrieri (dioscoreaceae) through anatomical and morphological characters / Nor Nafizah Mohd Noor ... [et al.] - Mohd Noor, Nor Nafizah; Wun, Shun Jie; Mohamed, Fatimah; Daud, Norhayati; Alimon, Hasimah (Universiti Teknologi MARA, Pulau Pinang, 2015)
Anatomy and morphological characters were employed to identify four samples of Tacca sp. (Belimbing Tanah) from different localities in Perak. Anatomical characters including leaf epidermal characters, leaf venation, type of stomata and trichomes were investigated through transverse sections, epidermal peel and leaf clearing procedures. The outline and vascularization of the sections were also investigated. Result has shown that Tacca from four different localities in Perak were similar anatomically. However, morphologically these four species can be differentiated mostly based on their leaves, flowers and fruits. The leaf margins are slightly different of either entire or denticulate, and the colours of floral bracts are either purplish-black or purplish-black at the base gradually turns white to the apex. Eventhough they are slightly different morphologically, Tacca of Gunung Lang and Gunung Liang were suggested as T. chantrieri based on dichotomous key of Kalkman which emphasizes on the shape of leaves, shape of seed and position of involucral bracts. The reniform shape of the seed confirms that these Tacca belong to T. chantrieri. Tacca of Sungai Dara and Royal Belum State Park were also suggested as T. chantrieri based on their anatomical similarity to Tacca of Gunung Lang and Gunung Liang. T. chantrieri is not commonly recorded in Peninsular Malaysia as compared to T. Intergrifolia, it is therefore recommended for further investigation.